Prevention of cyclophosphamide-induced hemorrhagic cystitis by resveratrol: a comparative experimental study with mesna - Keles, Ibrahim; Bozkurt, Mehmet Fatih; Cemek, Mustafa; Karalar, Mustafa; Hazini, Ahmet; Alpdagtas, Saadet; Keles, Hikmet; Yildiz, Turan; Ceylan, Cavit; Buyukokuroglu, Mehmet Emin (SPRINGER, 2014)
Hemorrhagic cystitis (HC) is the most common urotoxic side effect of cyclophosphamide (CP). The aim of this study was to compare the classical efficacy of mesna (2-mercaptoethane sulfonate sodium) with three different doses of resveratrol (RES) on cyclophosphamide-induced HC in rats. Forty-six male Sprague-Dawley rats were divided into six groups. Group 1 served as a negative control (sham). Five groups received a single dose of cyclophosphamide (150 mg/kg) intraperitoneally at the same time. Groups 2, 3, 4, 5, and 6 received only CP, CP + 20 mg/kg RES, CP + 40 mg/kg RES, CP + 80 mg/kg RES, and CP + classical protocol of three doses of mesna (30 mg/kg three times), respectively. Antioxidants, cytokines, and malondialdehyde levels were measured in all groups. In addition, histopathological alterations in tissues were examined. CP administration induced severe HC with marked edema, hemorrhage, and inflammation in group 2. RES 20 mg/kg showed meaningful protection against bladder damage compared to the control group. It was seen that RES 40 mg/kg gave weaker protection but RES 80 mg/kg was not found to be effective. In conclusion, marked bladder protection was found in 20 and 40 mg/kg RES applications compared to the control group, but this protection was weaker than with mesna.
Keywords: Hemorrhagic cystitis; Cyclophosphamide; Resveratrol; Mesna; Rat; INDUCED FANCONI-SYNDROME; DAMAGE; ANTIOXIDANTS; ACROLEIN; PROTECTS; OXYGEN; RATS; Urology & Nephrology